Lipopolysaccharide-induced changes in the hepatic transcriptome revealed breed-specific response in St. Croix and Suffolk sheep - Johnson, Samanthia R.; Bentley, Kelsey L.; Bowdridge, Scott A.; Ogunade, Ibukun M. (Frontiers in Animal Science, 2025)
This study aimed to investigate breed-specific differences in the liver transcriptomic response to lipopolysaccharide (LPS) in St. Croix (STC) and Suffolk (SUF) sheep. A total of 18 sheep (9 STC and 9 SUF) were administered LPS (E. coli O111), at a dosage of 2.5 mg/kg via I.V. After euthanasia, liver samples were collected at three time points: HR0 (n = 3 per breed; no LPS), HR2 (n = 3 per breed; 2 hours after LPS), and HR6 (n = 3 per breed; 6 hours after LPS). RNA sequencing and pathway enrichment analysis were conducted to assess differentially expressed genes (DEG; FDR ≤ 0.05) and associated biological processes. At baseline (HR0), 141 DEGs were identified between STC and SUF. SUF sheep upregulated pathways related to immune readiness, including defense responses and innate immune responses. At HR2, STC had 1,719 DEGs with top upregulated genes including SELE and CCL20. Alternatively, SUF had 2,742 DEGs at HR2, with similar immune response genes expressed but at lower magnitudes. At HR6, STC had a significant shift in gene expression, with 5,568 DEGs. Notably, STC shifted from immunity-related pathways to metabolic processes. In contrast, SUF had 5,862 DEGs at HR6, continuing to express pathways related to cytokine signaling and cellular responses. Overall, STC exhibited a more intense initial response to LPS, followed by a shift towards increased differential expression of genes associated with metabolism rather than immunity. SUF, however, maintained heightened immune activity even after 6 hours, suggesting a less effective resolution of the LPS-induced challenge.